2019
DOI: 10.2471/blt.18.217471
|View full text |Cite
|
Sign up to set email alerts
|

Implementing prevention policies for mother-to-child transmission of HIV in rural Malawi, South Africa and United Republic of Tanzania, 2013–2016

Abstract: Objective To assess adoption of World Health Organization (WHO) guidance into national policies for prevention of mother-to-child transmission (PMTCT) of human immunodeficiency virus (HIV) and to monitor implementation of guidelines at facility level in rural Malawi, South Africa and the United Republic of Tanzania. Methods We summarized national PMTCT policies and WHO guidance for 15 indicators across the cascades of maternal and infant care over 2013-2016. Two survey rounds were conducted (2013-2015 and 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…For example, providers in Ifakara reported not allowing other specified people to collect ART supplies for their client, and facilities in Ifakara and uMkhanyakude also reported only providing a onemonth supply of drugs, despite the national policy for multi-month scripting. Other studies have highlighted that flexible HIV care policies can lead to varied implementation (Ambia et al, 2017;Jones et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, providers in Ifakara reported not allowing other specified people to collect ART supplies for their client, and facilities in Ifakara and uMkhanyakude also reported only providing a onemonth supply of drugs, despite the national policy for multi-month scripting. Other studies have highlighted that flexible HIV care policies can lead to varied implementation (Ambia et al, 2017;Jones et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Other barriers and facilitators of transition included characteristics of the health facility and system. Although the WHO recommends interventions using case managers or navigators to enhance linkage between services, a review of PMTCT policy and policy implementation in Malawi, South Africa and Tanzania, found that most Malawian, but few other facilities implemented this and none had explicit guidance in their national policy [11]. There is a clear need for guidelines on the transition process and greater understanding by health providers and clients.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in transmission risk was first realized in the prevention of mother to child transmission (PMTCT). Initially pregnant women were treated with a single drug to prevent vertical transmission, (Newell, 2001) then with a combination of drugs during pregnancy for improved protection of infants (Mofenson, 2008), and finally in "B+" programs, where women were treated before during and after pregnancy to protect their own health and to prevent vertical transmission (Jones et al, 2019). Additional reductions in HIV incidence in young women where HIV programs have succeeded in reducing horizontal transmission have also contributed to the reduced acquisition of HIV in children.…”
Section: The Course Of the Hiv Pandemicmentioning
confidence: 99%